KAJIAN USAHA PETERNAKAN BABI DAN PEMASARANNYA DI KOTA KEFAMENANU, KABUPATEN TIMOR TENGAH UTARA (STUDI KASUS DI PETERNAKAN INDOMOR FARM) (Study of Pig Farming and Marketing in Kefamenanu City, Timor Tengah Utara Regency - Case Study at Indomor Farm) - Hembi, Yulius; Kadju, F. Y.D.; Sahala, J.; Simamora, T.; Gusri, R. (Universitas Nusa Cendana, 2025)
The development of the livestock sub-sector generally aims to increase farmers' income, accelerate the availability of quality food, and ensure meat quality, especially pork, so that it can be consumed by the community with optimal nutritional content. Pig farming is one of the livestock businesses that has long been popular among the people in the province of East Nusa Tenggara, especially in Kefamenanu City, Timor Tengah Utara Regency. The objective of this study is to identify pig farming businesses and their marketing systems in Kefamenanu City. The research was conducted at Indomor Farm as a case study of pig farming businesses in Kefamenanu City. The method used in this study was a survey analyzed descriptively with a quantitative approach. Based on the analysis results, it can be concluded that: (1) There is only one marketing channel pattern for pork in Kefamenanu City, namely: Farmer - Livestock Slaughterer/Retailer - Consumer; and (2) The margin per kilogram of output produced by the pork marketing institution is Rp63.555,55 for farmers and Rp8.855,84 for livestock slaughterers/retailers. Overall, the pig farming business in Kefamenanu City is a viable and profitable venture to undertake.